Mario Osorio Marques: Conversation leads to Conversation! (Revista Contexto & Educação, 2025)
This essay is a homage to Professor Mario Osorio Marques, based on personal memories and notes from the period in which I was a student in the Master's Program in Education in the Sciences, as proposed by the commemorative dossier marking the centenary of this great educator's birth. Using narrative as a methodological approach, I express the pride of having joined the third cohort of this innovative and bold initiative: a master’s program offered in the interior of Rio Grande do Sul, a region then considered economically disadvantaged. Mario Osorio Marques was a pioneer in the expansion of higher education and in the implementation of graduate (stricto sensu) programs in the northwestern region of our state, through UNIJUÍ, the university he helped to establish. He was an educator who consistently sought to align his actions with his words and writings, living by the principles he advocated—whether in casual conversation or while teaching. A great master, professor, and visionary, he fulfilled his mission of promoting quality education and regional development, grounded in the potential to overcome social and regional inequalities. Mario Osorio Marques was—and continues to be—fundamental to the pursuit of quality education for all, with a focus on quality of life. For this reason, even if it may seem prescriptive, it is necessary to reintegrate his thought into the required reading of teacher education programs, through his published works and articles. Moreover, it is essential to revive his vision and belief in education as a fundamental phenomenon of human life, a message he consistently conveyed in his teachings and writings.
Keywords: Education; Mario Osorio Marques; Regional Development; Legacy